2020
DOI: 10.1080/15384047.2020.1843897
|View full text |Cite
|
Sign up to set email alerts
|

miR-219a-1 inhibits colon cancer cells proliferation and invasion by targeting MEMO1

Abstract: Colon cancer is the third most common cancer worldwide. Many miRNAs have been reported to be involved in colon cancer progression. However, there are only a few studies on the role of miR-219a-1 in colon cancer, and the molecular mechanisms involved remain unclear. The aim of this study was to investigate the miR-219a-1 level in patients with colon cancer and to explore both the effects and regulatory mechanisms of miR-219a-1 in the malignancy of colon cancer cells. Real-time PCR and western blot analysis were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…The progression of colon cancers involved lots of miRNAs, such as miR-141 [ 35 ], miR-219a-1 [ 36 ], and miR-503-5p [ 37 ]. MiR-338-3p, a miRNA, was found to play vital parts in colon cancer cell processes.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of colon cancers involved lots of miRNAs, such as miR-141 [ 35 ], miR-219a-1 [ 36 ], and miR-503-5p [ 37 ]. MiR-338-3p, a miRNA, was found to play vital parts in colon cancer cell processes.…”
Section: Discussionmentioning
confidence: 99%
“…MEMO1 plays an important role in breast cancer cell invasion and migration by activating the PI3K/Akt signaling pathway, leading to up-regulated Snail1 and induction of the EMT program[ 21 ]. MEMO1 is highly expressed in colon cancer tissues and cells, and miR-219a-1 regulates the proliferation, invasion and metastasis of colon cancer cells by targeting MEMO1, thereby functioning as a tumor suppressor gene[ 22 ]. The role of MEMO1 in the progression of GC has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that miRNAs regulate components of the PI3K/Akt signalling pathway ( Rahmani et al, 2020a ; Rahmani et al, 2020b ), and abnormal expression of these miRNAs might induce an out-of-control expression of their targets, which leads to disorders of the corresponding signalling pathway ( Akbarzadeh et al, 2021 ). Studies have observed the abnormal expression of miR-219a ( Xu et al, 2020 ), let-7i ( Chhabra, 2018 ), miR-149 ( Zhou and Xu, 2021 ), miR-143 ( Tang et al, 2021 ), miR-132 ( Zhang et al, 2021 ), miR-10b ( Zou et al, 2016 ), let-7a ( Wu et al, 2016 ) and miR-26a ( Dong et al, 2014 ) in CC or other human cancers, which indicated the important roles of these miRNAs in human cancers. Single nucleotide polymorphisms (SNPs) in miRNA genes can modify the expression of mature miRNAs ( Slezak-Prochazka et al, 2010 ; Króliczewski et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%